Effect of Soil-Structure Interaction on the Response of Machine Foundation Subjected to Seismic Loading: A Review Study (Journal of Engineering, 2024)
This review provides a detailed look at the current knowledge and approaches related to Dynamic Soil-Structure Interaction (DSSI) in machine foundation design, focusing on its substantial impact on seismic response and structural stability. The significance of this interaction in structural design, especially in areas prone to seismic activity, is pivotal. The paper begins by exploring various modeling methods, like the Finite Element Method (FEM), highlighting their importance in understanding the intricate aspects of DSSI, such as energy loss and interface behavior. It is evident from the studies that FEM is particularly effective in analyzing settlement under reciprocating loads. Soil-structure interaction (SSI) is a complex phenomenon that can positively and negatively affect the seismic performance of machine foundations. Several factors, including embedment depth, soil stiffness, and foundation properties, govern the influence of SSI. This review discusses the dual nature of SSI and highlights the importance of considering the interaction between soil properties, foundation design, seismic loads, and interaction effects. In addition, it identifies the limitations of the current research and advocates for more accurate and inclusive models and extensive empirical studies to address real-world complexities and uncertainties. In conclusion, this review offers crucial insights and foundational knowledge for future innovative design solutions and advanced research methodologies and significantly contributes to developing resilient and reliable structural designs in seismic-prone regions. The emphasis is on the need for more nuanced and comprehensive studies to further the understanding and application of DSSI in machine foundation design.